2008
DOI: 10.1097/aln.0b013e3181684bc3
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil Inhibits Rapid Eye Movement Sleep but Not the Nocturnal Melatonin Surge in Humans

Abstract: Background: Postoperative patients are sleep deprived. Opioids, commonly administered for postoperative pain control, are often mistakenly considered inducers of naturally occurring sleep. This study describes the effect of the opioid remifentanil on nocturnal sleep in healthy volunteers. In addition, this study tests the hypothesis that opioid-induced sleep disturbance is caused by a circadian pacemaker disturbance, reflected by suppressed nocturnal plasma concentration of melatonin.Methods: Polysomnography w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 35 publications
(26 reference statements)
3
25
0
1
Order By: Relevance
“…To our knowledge, this is the first time melatonin secretion pattern is investigated under remifentanil infusion in critically ill patients. Nevertheless, our results are in line with the study by Bonafide et al, where melatonin secretion was investigated in healthy participants under sedation with remifentanil and found preserved [18]. The relatively small doses of remifentanil used in both studies may possibly explain the missing effect of remifentanil on melatonin secretion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, this is the first time melatonin secretion pattern is investigated under remifentanil infusion in critically ill patients. Nevertheless, our results are in line with the study by Bonafide et al, where melatonin secretion was investigated in healthy participants under sedation with remifentanil and found preserved [18]. The relatively small doses of remifentanil used in both studies may possibly explain the missing effect of remifentanil on melatonin secretion.…”
Section: Discussionsupporting
confidence: 92%
“…However, remifentanil was not found to have the same effect on acetylcholine as morphine and fentanyl in the study by Mortazavi et al [5]. Bonafide et al investigated the effect of remifentanil on sleep in healthy humans and found reduced REM sleep [18]. In line with this study, we only observed REM sleep in the epochs recorded under the period without remifentanil.…”
Section: Discussionsupporting
confidence: 81%
“…Some believe that medications from the agonist/antagonist class, such as buprenorphine, may be less associated with the adverse effects of traditional μ-agonists; however, the present data indicate that the sleep-disrupting effects of buprenorphine are similar to those of other opioids. 26,30,37,53 The present results encourage studies designed to objectively quantify the effects of buprenorphine on sleep in humans.…”
Section: Discussionsupporting
confidence: 53%
“…52 The chronic effects of μ-opioid receptor agonists on sleep in pain patients are not completely understood. 39 Opioids cause sleep disturbance 4,37,53 and the present results demonstrate that buprenorphine increases wakefulness and disrupts the temporal organization of sleep (figs. 2-4).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation